DETERMINANTS,CHARACTERISTICS AND PREFORMANCE OF THE GROWTH OF MICRO AND SMALL ENTERPRISES (MSE): A SYSTEMATIC REVIEW OF EVIDENCE FROM ETHIOPIA. - Tolesa, Shibeshi Fekadu (The journal of contemporary issues in business and government, 2024)
Micro and Small Enterprises (MSE) are now the center of attention for global economic development, employment creation, and growth. Micro and small enterprises account for the majority of businesses globally.The informal sector, which mostly creates MSE, continues to be the main source of employment and income for the populace in developing nations, particularly in Ethiopia.In 2011, the plan was updated with fresh focus and more aggressive goals for employment and the percentage of businesses moving up to a medium level. Nevertheless, despite their efforts, MSEs in Ethiopia face numerous challenges, which leads to poor performance and a failure to make the necessary contributions from many MSEs. Therefore, in order to boost MSE growth and performance and improve their contribution to the growth of the national economy, the government should place a strong emphasis on procedures for addressing these issues.